Empty pastures : confined animals and the transformation of the rural landscape - Centner, Terence J. (Book collections on Project MUSE., 2004)
Annotation "Over the past century American agriculture has shifted dramatically, with small, commercial farms finding it increasingly difficult to compete with large-scale (mostly indoor) animal feeding operations (AFOs). In this book Terence J. Centner investigates environmental, social, economic, and political considerations related to the rise of the so-called factory farm, exposing the ramifications of the contemporary trend toward industrial-scale food productions." "Just as Rachel Carson's landmark Silent Spring used the disappearance of songbirds as a jumping-off point for a work that raised public awareness of pesticides' devastating environmental impact, Empty Pastures sees the dwindling numbers of livestock in the American countryside as a symptom of a broader transformation, one with serious consequences for the rural landscape and its inhabitants - animal as well as human." "After outlining the rise of the AFO, Centner examines the troubling consequences of consolidation in animal farming and suggests a number of rememdies. The issues he tackles include groundwater contamination, the loss of biodiversity, animal welfare, concentrated odors and other nuisances, soil erosion, and the economic effects of the disappearance of the small family farm."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved